The androgen receptor gene CAG repeat in relation to 4-year changes in androgen-sensitive endpoints in community-dwelling older European men. Issue 6 (December 2016) - Eendebak, Robert J A H; Huhtaniemi, Ilpo T; Pye, Stephen R; Ahern, Tomas; O'Neill, Terence W; Bartfai, György; Casanueva, Felipe F; Maggi, Mario; Forti, Gianni; Alston, Robert D; Giwercman, Aleksander; Han, Thang S; et al.
Abstract : Context: The androgen receptor ( AR ) gene exon 1 CAG repeat length has been proposed to be a determinant of between-individual variations in androgen action in target tissues, which might regulate phenotypic differences of human ageing. However, findings on its phenotypic effects are inconclusive. Objective: To assess whether the AR CAG repeat length is associated with longitudinal changes in endpoints that are influenced by testosterone (T) levels in middle-aged and elderly European men. Design: Multinational European observational prospective cohort study. Participants: A total of 1887 men (mean ± s.d. age: 63 ± 11 years; median follow up: 4.3 years) from centres of eight European countries comprised the analysis sample after exclusion of those with diagnosed diseases of the hypothalamic–pituitary–testicular (HPT) axis. Main outcome measures: Longitudinal associations between the AR CAG repeat and changes in androgen-sensitive endpoints (ASEs) and medical conditions were assessed using regression analysis adjusting for age and centre. The AR CAG repeat length was treated as both a continuous and a categorical (6–20; 21–23; 24–39 repeats) predictor. Additional analysis investigated whether results were independent of baseline T or oestradiol (E2 ) levels. Results: The AR CAG repeat, when used as a continuous or a categorical predictor, was not associated with longitudinal changes in ASEs or medical conditions after adjustments. These results were independent of T and E2 levels. Conclusion: Within a 4-year time frame, variations in the AR CAG repeat do not contribute to the rate of phenotypic ageing, over and above, which might be associated with the age-related decline in T levels.